Genetic variant near IRS1 is associated with type 2 diabetes, insulin resistance and hyperinsulinemia - Rung, Johan; Cauchi, Stéphane; Albrechtsen, Anders; Shen, Lishuang; Rocheleau, Ghislain; Cavalcanti-Proença, Christine; Bacot, François; Balkau, Beverley; Belisle, Alexandre; Borch-Johnsen, Knut; Charpentier, Guillaume; Dina, Christian; et al. (Nature genetics, 2009)
Rob Sladek and colleagues identify a common variant near the insulin receptor substrate 1 gene ( IRS1 ) associated with type 2 diabetes, insulin resistance, hyperinsulinemia and impaired insulin signaling. This is the first confirmed diabetes risk locus associated with insulin resistance. Genome-wide association studies have identified common variants that only partially explain the genetic risk for type 2 diabetes (T2D). Using genome-wide association data from 1,376 French individuals, we identified 16,360 SNPs nominally associated with T2D and studied these SNPs in an independent sample of 4,977 French individuals. We then selected the 28 best hits for replication in 7,698 Danish subjects and identified 4 SNPs showing strong association with T2D, one of which (rs2943641, P = 9.3 × 10 −12 , OR = 1.19) was located adjacent to the insulin receptor substrate 1 gene ( IRS1 ). Unlike previously reported T2D risk loci, which predominantly associate with impaired beta cell function, the C allele of rs2943641 was associated with insulin resistance and hyperinsulinemia in 14,358 French, Danish and Finnish participants from population-based cohorts; this allele was also associated with reduced basal levels of IRS1 protein and decreased insulin induction of IRS1-associated phosphatidylinositol-3-OH kinase activity in human skeletal muscle biopsies.